Pengaruh Influencer Terhadap Minat Beli Emina dengan Mediasi Brand Awareness - Putri Rahmadani; Lena Ellitan (Universitas Katolik Darma Cendika, 2026)
This study aims to analyze the influence of celebrity influencer credibility, celebrity influencer attractiveness, and attitude, mediated by brand awareness, on the purchase intention of Emina products in Surabaya and outside Surabaya. This research employs a quantitative method with a descriptive approach. Data was collected through a questionnaire link distributed to respondents who met specific criteria. The respondents in this study are consumers of Emina products residing in Surabaya and other cities. The sampling technique used was non-probability sampling, with a total of 168 respondents. The data were analyzed using SEM-PLS 4.0. The results of this study indicate that celebrity influencer credibility has a positive and significant effect on attitude. Celebrity influencer attractiveness does not have a positive or significant effect on attitude. Attitude has a positive and significant effect on brand awareness. Brand awareness has a positive and significant effect on attitude. Furthermore, attitude towards purchase intention, mediated by brand awareness, has a positive and significant effect. This study provides valuable insights for companies in designing marketing strategies to enhance consumer purchase decisions for Emina products.